1990
DOI: 10.1079/bjn19900064
|View full text |Cite
|
Sign up to set email alerts
|

Body composition of goat kids during sucking. Voluntary feed intake

Abstract: -The body composition of thirty-eight Granadina goat kids was measured. Six animals were slaughtered at birth while the remainder were kept individually at an environmental temperature of 24k2" and a relative humidity of 60 & 5 YO. They were given goat's milk or a milk-substitute at two planes of nutrition until 15 or 30 d of age and then slaughtered. The goat's milk and milk-substitute contained 2604 and 222.0 g digestible protein/kg and 23.23 and 20.85 MJ metabolizable energylkg respectively. Voluntary feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…The liveweight gains are similar to those with milk replacer or goat milk reported by Sanz Sampelayo et al (1987Sampelayo et al ( , 1988Sampelayo et al ( , 1990. As expected, in the present experiment milk replacer intake and liveweight gain in weeks 1 to 4 and 5 to 8 were greater for males than for females.…”
Section: Discussionsupporting
confidence: 77%
“…The liveweight gains are similar to those with milk replacer or goat milk reported by Sanz Sampelayo et al (1987Sampelayo et al ( , 1988Sampelayo et al ( , 1990. As expected, in the present experiment milk replacer intake and liveweight gain in weeks 1 to 4 and 5 to 8 were greater for males than for females.…”
Section: Discussionsupporting
confidence: 77%
“…In this context, the maximum feed intake of the kid goat has been found to be low in comparison with other pre-ruminants. Sanz Sampelayo et al (1990b) reported that for the first month of life, empty-body composition of kids depended on empty-body weight, independently of intake level and even of dietary regimen. However, in older or heavier kids, which are those considered ideal for slaughter, results indicate that the dietary regimen and level of feed intake do have some effect on the body composition Bas etal.…”
mentioning
confidence: 99%
“…This difference was probably due to a lower daily ME intake in the present study (1025 vs. 1244 and 1068 kJ/kg BW 0.75 /d). Correcting for an MEm of 429 kJ/kg BW 0.75 (Sanz Sampelayo et al, 1990), the ME per gram of ADG was similar in the three experiments (4.97 vs. 5.03 and 4.73 kJ/kg BW 0.75 /d). All the data on BW, weight gain and ME intake (n = 60) was used to assess the accuracy of NRC (2007) to predict the ME requirements.…”
mentioning
confidence: 82%
“…Sanz Sampelayo et al (1990) found that the ME intake in preruminant Murciano-Granadina male kids, up to 30 days of age, fed milk replacer was 2.4 times the MEm requirements. Assuming that the MEm requirements are 429 kJ/kg BW 0.75 (Sanz Sampelayo et al, 1990) or 449 kJ/kg BW 0.75 , it was calculated that ME intake was 2.39 ± 0.17 or 2.28 ± 0.16 times the MEm requirements. Both the MEm and ME intake were correlated (r = 0.91, P <0.05), supporting Sanz Sampelayo et al (1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation